Design, Fabrication & Experimental Analysis Of Automatic Solar Tracking System For Parabolic Trough Collector For Hot Water Generation - Singh, Pardeep (My University, 2013)
In this world, everyone needs energy for day to day living cycle. Sources of energy are depleting at a very fast rate. There is need to explore renewable energy sources which are more efficient and give low operating cost. Sun is a source of renewable energy. Solar energy is a basic need of living plants and human being on the earth. It is intermittent in nature, eco-friendly and non-polluting energy. It is freely available throughout the world. Solar energy can be used for hot water generation and direct conversion into electricity and into thermal energy. A parabolic trough solar collector uses the glass mirror as reflecting material in the shape of parabola to reflect and concentrate the sun radiation towards a receiver tube located at the focus of the parabola. Various solar tracking systems have been developed by various researchers in past decades. A tracking system is still required which can track the sun on real time basis without any geographical data. In the present work an automatic sun tracking system for parabolic trough collector is designed fabricated and experimental analysis is carried out for its feasibility in hot water generation. After experimental work it is found that the automatic sun tracking system gives more efficiency as compare to manual and fixed collectors. In the present work two axis of motion (horizontal and vertical axis) are controlled by using different light detector, DC motors, and gear mechanism. A black painted copper tube is used as an absorber tube and a glazing (glass cover tube of bigger diameter) is provided to minimize the conduction, convection and radiation losses. Water is used as a heat carrying fluid in absorber tube. The concentration ratio of the PTC is 9.66 with aperture area 1.1163 m2 (without glazing) and 1.035 m2 with glazing. The maximum temperature of heating water obtained is 85℃ while the average temperature of heating water was produced is 68℃. The improvement in efficiency using automatic sun tracking system as compare to manual and fixed position tracking system is 20 to 40%. The results obtained shows that the production of heating water using sun flux is a viable undertaking using automatic solar tracking system. Reduced mass flow rate or with different mass flow rate the efficiency of PTC can further be increased.
ME, MED
Keywords: Automatic Solar Tracking; Hot Water Genaration; Parabolic Trough collector